Gene Expression and Proteome Analysis as Sources of Biomarkers in Basal Cell Carcinoma. (8th August 2016) - Lupu, Mihai; Caruntu, Constantin; Ghita, Mihaela Adriana; Voiculescu, Vlad; Voiculescu, Suzana; Rosca, Adrian E.; Caruntu, Ana; Moraru, Liliana; Popa, Iris Maria; Calenic, Bogdan; Greabu, Maria; Costea, Daniela Elena
Abstract : Basal cell carcinoma (BCC) is the world's leading skin cancer in terms of frequency at the moment and its incidence continues to rise each year, leading to profound negative psychosocial and economic consequences. UV exposure is the most important environmental factor in the development of BCC in genetically predisposed individuals, this being reflected by the anatomical distribution of lesions mainly on sun-exposed skin areas. Early diagnosis and prompt management are of crucial importance in order to prevent local tissue destruction and subsequent disfigurement. Although various noninvasive or minimal invasive techniques have demonstrated their utility in increasing diagnostic accuracy of BCC and progress has been made in its treatment options, recurrent, aggressive, and metastatic variants of BCC still pose significant challenge for the healthcare system. Analysis of gene expression and proteomic profiling of tumor cells and of tumoral microenvironment in various tissues strongly suggests that certain molecules involved in skin cancer pathogenic pathways might represent novel predictive and prognostic biomarkers in BCC.